Cell Calcium Imaging as a Reliable Method to Study Neuron–Glial Circuits - de Melo Reis, Ricardo Augusto; Freitas, Hércules Rezende; de Mello, Fernando Garcia (Frontiers in Neuroscience, 2020)
Complex dynamic cellular networks have been studied in physiological and pathological processes under the light of single-cell calcium imaging (SCCI), a method that correlates functional data based on calcium shifts operated by different intracellular and extracellular mechanisms integrated with their cell phenotypes. From the classic synaptic structure to tripartite astrocytic model or the recent quadripartite microglia added ensemble, as well as other physiological tissues, it is possible to follow how cells signal spatiotemporally to cellular patterns. This methodology has been used broadly due to the universal properties of calcium as a second messenger. In general, at least two types of receptors operate through calcium permeation: a fast-acting ionotropic receptor channel, and a slow activating metabotropic receptor, added to exchangers/transporters/pumps and intracellular Ca2+ release-activated by messengers. These prototypes have gained an enormous amount of information in dynamic signaling circuits. SCCI has also been used as a method to associate phenotypic markers during development and stage transitions in progenitors, stem, vascular cells, neuro- and glioblasts, neurons, astrocytes, oligodendrocytes and microglia that operate through ion channels, transporters, and receptors. Also, cancer cells or inducible cell lines from human organoids characterized by transition stages are currently been used to model diseases or reconfigure healthy cells in terms of expression of calcium-binding/permeable molecules and shed light on therapy.